2004
DOI: 10.1007/bf03018553
|View full text |Cite
|
Sign up to set email alerts
|

High frequency oscillatory ventilation in the management of a high output bronchopleural fistula: a case report

Abstract: We report the successful use of HFOV in a patient with high output BPF. We suggest that HFOV is a useful technique in patients with a BPF when conventional positive pressure ventilation fails.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 25 publications
1
17
0
1
Order By: Relevance
“…2 In a recent case report, HFOV has been described as a useful technique to manage a high output BPF when conventional positive pressure ventilation failed. 5 However, older studies did not show better outcomes in terms of gas exchange, airway pressures, or air leak. 6,7 Few articles describe the combination of high frequency ventilation with spontaneous breathing.…”
Section: Discussionmentioning
confidence: 98%
“…2 In a recent case report, HFOV has been described as a useful technique to manage a high output BPF when conventional positive pressure ventilation failed. 5 However, older studies did not show better outcomes in terms of gas exchange, airway pressures, or air leak. 6,7 Few articles describe the combination of high frequency ventilation with spontaneous breathing.…”
Section: Discussionmentioning
confidence: 98%
“…[8][9][10][11] Furthermore, anecdotal reports suggest that HFOV may be effective in adults with bronchopleural fistula. 3,4 Ha et al reported a 55-year-old with empyema who developed bronchopleural fistula following decortication. 4 There was substantial air leak via the bronchopleural fistula with the high PIP on conventional mechanical ventilation, but HFOV was associated with much less air leak and improved oxygenation and ventilation in that patient.…”
Section: Discussionmentioning
confidence: 99%
“…4,6 Persistent bronchopleural fistula during mechanical ventilation can lead to pneumothorax and ventilation-perfusion mismatch. 6 Since much of the inspired volume exits through the fistula rather than going to the alveoli, alveolar ventilation may profoundly decrease and cause moderate to severe respiratory acidosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ventilator strategies utilizing reduced tidal volumes, PEEP, and inspiratory times are used to limit air flow through a BPF and promote healing [81][82][83][84]. Additional alternative methods of ventilation have also been tried including selective intubation of the healthy lung, double lumen intubation with independent ventilation, high-frequency oscillatory ventilation, high-frequency jet ventilation, and extracorporeal support methods [81,82,85,86]. Differential lung ventilation with either selective mainstem bronchial intubation or double lumen intubation reduces or eliminates air flow to the lung with the BPF but requires the unaffected lung to be healthy enough to support ventilation and oxygenation.…”
Section: Persistent Bronchopleural Fistulamentioning
confidence: 99%